A Small Molecule Antagonist of PD-1/PD-L1 Interactions Acts as an Immune Checkpoint Inhibitor for NSCLC and Melanoma Immunotherapy - Wang, Yuanyuan; Gu, Tingxuan; Tian, Xueli; Li, Wenwen; Zhao, Ran; Yang, Wenqian; Gao, Quanli; Li, Tiepeng; Shim, Jung-Hyun; Zhang, Chengjuan; Liu, Kangdong; Lee, Mee-Hyun (Frontiers in Immunology, 2021)
Until now, monoclonal antibody (mAb) targeting the immune checkpoint programmed death 1 (PD-1) and its ligand programmed death ligand-1 (PD-L1) attained enormous success in anticancer therapy; however, due to expensive, poor tumor penetration and high autoimmune side effect level, mAbs cause to limit applying to patients. Here we offer evidence that PD1/PD-L1 inhibitor 1 (PDI-1) as a small-molecule antagonist is capable of diminishing the PD-1/PD-L1 immune checkpoint-mediated exhaustion of T-lymphocytes. PDI-1, predicted by the computational docking model, can bound to human and mouse PD-1 and PD-L1 in vitro and in vivo. PDI-1 could block the interaction between PD-1 and PD-L1 and enhance T cell activity by restoring the TCR-CD28 signaling pathway, thus induce immunogenic cell death of lung cancer and melanoma in vivo. We also investigated the effect of PDI-1 in PD-L1 humanized syngeneic murine model, and the results showed PDI-1 retarded tumor growth of PD-L1 humanized NSCLC and melanoma syngeneic murine model by increasing the T cell infiltrations and its related cytokines.